2015
DOI: 10.5792/ksrr.2015.27.4.228
|View full text |Cite
|
Sign up to set email alerts
|

Anterolateral Portal Is Less Painful than Superolateral Portal in Knee Intra-Articular Injection

Abstract: PurposeIntra-articular knee injections are commonly performed in clinical practice for treating various knee joint disorders such as osteoarthritis and rheumatoid arthritis. When selecting the portal for injection, not only intra-articular needle accuracy but also procedural pain should be taken into consideration. The purpose of this study was to determine whether injection through anterolateral portal provokes less pain and provides better pain relief compared to superolateral portal.Materials and MethodsA t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 15 publications
0
9
1
Order By: Relevance
“…An increase in BMI seems to be a predictor of pain in anterolateral access. Our pain VAS results are partially in contrast with previous findings: Chavez-Chiang et al [ 10 ] reported a mean VAS pain score of 4.8 for anterolateral access, while Lee et al [ 11 ] found that the anterolateral approach is less painful than superolateral. We could hypothesize that such differences might be related to the use of a thinner 21-gauge needle than Lee’s cohort [ 11 ]; moreover, operator expertise and grade of local joint inflammation may be taken into account in order to explain the different outcomes.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…An increase in BMI seems to be a predictor of pain in anterolateral access. Our pain VAS results are partially in contrast with previous findings: Chavez-Chiang et al [ 10 ] reported a mean VAS pain score of 4.8 for anterolateral access, while Lee et al [ 11 ] found that the anterolateral approach is less painful than superolateral. We could hypothesize that such differences might be related to the use of a thinner 21-gauge needle than Lee’s cohort [ 11 ]; moreover, operator expertise and grade of local joint inflammation may be taken into account in order to explain the different outcomes.…”
Section: Discussioncontrasting
confidence: 99%
“…In clinical practice, knee injection is a very well tolerated therapeutic option. In the literature, few papers have assessed injection related pain in knee OA, with contrasting outcomes between pain difference for the two techniques [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] If this positioning results in no fluid return the needle is manipulated into the patellofemoral joint and the intracondylar notch. [1][2][3][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] However, even with this standard extended knee approach, after conventional arthrocentesis typically there is considerable residual synovial fluid remaining in the joint (approximately 30%-40%), thus, full fluid extraction using conventional arthrocentesis even in the extended positioning is incomplete. 27 Although the extended knee superolateral suprapatellar bursa approach is the traditional anatomic puncture point for arthrocentesis, there are a number of advantages to the anterolateral portal flexed knee approach for arthrocentesis and joint injection.…”
Section: Discussionmentioning
confidence: 99%
“…The anterolateral portal was defined by palpation of the adjoining structures of anterolateral border of the patella, the lateral border of the patellar tendon, and the anterolateral tibial plateau with the entry point adjacent to the lateral patellar tendon, thus avoiding the lateral geniculate artery. [12][13][14][15] The anterolateral portal was thus determined and marked with the tip of a retractable ballpoint pen with the point retracted leaving a depression in the skin. A thigh blood pressure leg cuff (HCS 9029LF, Cuff and Bladder Latex-Free, Thigh Size, Sphygmomanometer, Dyad Medical Sourcing, LLC, Bannockburn, IL, USA) was placed around the superior flexed knee where it surrounded the upper leg and the suprapatellar bursa (Figure 1).…”
Section: Arthrocentesis Techniquementioning
confidence: 99%
“…Patients that met our inclusion criteria were informed about our study design and objective and after signing the informed consent they received two consecutive intraarticular injections of 24 mg/3 ml of (500-730 kDa) modified HA (Hymovis®, Fidia Farmaceutici S.p.A, Italy) at one-week interval. As the anterolateral portal proved to be less painful in intraarticular administration of treatments [18], all injections were performed in the outpatient clinic under aseptic conditions in the aforementioned location. Follow-up visits were scheduled at 6 and 12 months after the injections.…”
Section: Methodsmentioning
confidence: 99%